2009
DOI: 10.21273/hortsci.19.4.792
|View full text |Cite
|
Sign up to set email alerts
|

Large Single-head Broccoli Yield as Affected by Plant Density, Nitrogen, and Cultivar in a Plasticulture System

Abstract: An open-market window has been identified in Virginia for fall broccoli (Brassica oleracea var. italica). Vegetable producers using plasticulture systems can capitalize on this opportunity by growing broccoli as a second crop after summer vegetables. The objective of this project was to evaluate suitability of two broccoli cultivars, Everest and Gypsy, for the fall production of large single-heads (>6 inches in diameter) for the fresh market. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…The highest total yield was recorded in N 3 (145.47 q/ha) followed by N 2 (143.11 q/ha), and lowest yield was obtained in N 1 (134.19 q/ha). Similar results were also reported by Bashyal et al, (2013); El-Helaly, ((2012); Schellenberg et al, (2009); Yoldas et al, (2008);Monirruzaman et al, (2007) at their place in broccoli. The intercropping systems showed nonsignificant variation for total yield of broccoli.…”
Section: Weight Of Axillary Sprouts Per Plant (G): Results Presented Insupporting
confidence: 88%
“…The highest total yield was recorded in N 3 (145.47 q/ha) followed by N 2 (143.11 q/ha), and lowest yield was obtained in N 1 (134.19 q/ha). Similar results were also reported by Bashyal et al, (2013); El-Helaly, ((2012); Schellenberg et al, (2009); Yoldas et al, (2008);Monirruzaman et al, (2007) at their place in broccoli. The intercropping systems showed nonsignificant variation for total yield of broccoli.…”
Section: Weight Of Axillary Sprouts Per Plant (G): Results Presented Insupporting
confidence: 88%
“…Eastern vegetable growers have typically used lower plant densities than those tested in this study. This may be largely due to the recommendations made by eastern researchers (i.e., Dufault and Waters 1985;Schellenberg et al, 2009). Several earlier studies evaluating plant density effects on broccoli production were done several decades ago when higher populations were being tested for western production systems (Cutcliffe, 1971(Cutcliffe, , 1975Palevitch, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Jett et al (1995) found no significant effect of plant density on days to harvest in a 1990 trial, but observed that days to harvest was up to 9 d later with a density of 108,000 plants/ha compared with that of 36,000 plants/ha in a 1991 trial. In another Virginia study, Schellenberg et al (2009) examined plant densities ranging from 18,000 to 48,000 plants/ha and within-row spacing of 9 to 24 inches, respectively, using the more modern hybrid 'Gypsy' as well as the older 'Everest' in a plasticulture system. This study found that 'Gypsy' was the preferred cultivar using a plant density of 35,000 plants/ha, yielding 11,500 kgÁha -1 .…”
mentioning
confidence: 99%
“…The seedlings were transplanted on 15 Feb. 2017 into the study field, covered with black plastic mulch and placed in transparent low plastic tunnels (PVC film, 0.075 mm thickness) at a planting density of 1.6 plants•m −2 (160 cm between ridges and 40 cm between plants). The practical density for heading type broccoli is 3.0-3.6 plants•m −2 (Jett et al, 1995;Schellenberg et al, 2009), but we set approximately half of this density to accommodate the development of branches. The field was fertilized with N, P 2 O 5 , and K 2 O at rates of 4, 4, and 3 kg•a −1 , respectively.…”
Section: Analysis Of Shoot Part Ratios (Exp 1)mentioning
confidence: 99%